Pengaruh Kompetensi SDM Terhadap Kinerja Usaha pada UMKM Sentra Kertabumi Karawang - Zenita Apriani; Shandikha Arya Yudha Rahman; Dini Yani; Ery Rosmawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The development of the MSME culinary industry is currently increasing, because culinary is a daily need for society. However, along with the development of the culinary era, it has not only become a consumer product, but now culinary has become a lifestyle for people. This research aims to determine the influence of entrepreneurial competence on the performance of Kertabumi Karawang MSMEs. This research uses quantitative research. The data collection techniques used are questionnaires, interviews, and observation of conditions at the research site. Testing the hypothesis in this research uses simple regression analysis. The results of this research show that competency has a significant positive effect on MSME business performance, increasing HR competency is a key strategy for improving MSME performance in the Kertabumi Karawang Center. Implementing competency improvement programs can help MSMEs become more competitive in local and regional markets.